Implementasi RTRW Kota Bengkulu terhadap Pembangunan Infrastruktur Jalan Tahun 2021–2024 - Yurisman Star; Desmar Panggarbesi (PERSPEKTIF, 2026)
This study examines the implementation of Bengkulu City Regional Regulation Number 4 of 2021 concerning the Regional Spatial Plan (RTRW) for 2021–2041 in road infrastructure development. The main issue addressed in this study is the unequal distribution of road development, particularly in suburban areas where damaged, pothole-ridden, and unpaved roads are still commonly found. This research employed a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The findings reveal that the implementation of the RTRW regulation has been carried out through planning, budgeting, implementation, and supervision stages by the Bengkulu City Public Works and Spatial Planning Agency (PUPR). However, the realization of road development during 2021–2024 has not been stable and is highly influenced by limited regional budgets and dependence on Special Allocation Funds from the central government. Communication, resources, implementer disposition, and bureaucratic structure also affect the effectiveness of policy implementation. The study concludes that the implementation of the RTRW regulation in road infrastructure development remains partial due to the gap between spatial planning objectives and actual field conditions. Therefore, stronger planning integration, fiscal capacity, intersectoral coordination, and community participation are needed.